2019
DOI: 10.1371/journal.pone.0225523
|View full text |Cite
|
Sign up to set email alerts
|

Quality and utilization patterns of maternity waiting homes at referral facilities in rural Zambia: A mixed-methods multiple case analysis of intervention and standard of care sites

Abstract: IntroductionMaternity waiting homes, defined as residential lodging near a health facility, are recommended by the WHO. An improved MWH model, responsive to community standards for functionality and comfort, was implemented at two purposively selected health facilities in rural Zambia providing comprehensive emergency obstetric and neonatal care (CEmONC) services (intervention MWHs), and compared to three existing standard-of-care MWHs (comparison MWHs) at other CEmONC sites in the same districts.MethodsWe use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…In terms of PNC, our findings are consistent with those of researchers in Zambia’s Southern and Eastern Provinces who used a time-series design to examine pre-post MWH intervention trends [ 30 ]. Researchers found the use of MWHs for PNC increased at one of two intervention sites even though both sites had dedicated space for PNC users [ 30 ]. Postnatal care is directly associated with place of birth and delivery by a skilled health provider [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…In terms of PNC, our findings are consistent with those of researchers in Zambia’s Southern and Eastern Provinces who used a time-series design to examine pre-post MWH intervention trends [ 30 ]. Researchers found the use of MWHs for PNC increased at one of two intervention sites even though both sites had dedicated space for PNC users [ 30 ]. Postnatal care is directly associated with place of birth and delivery by a skilled health provider [ 28 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…Levels of MWH utilization globally have been reported to be sub-optimal, partly due to the poor quality of services available at MWHs [ 17 ]. A recent Zambian study using upgraded MWHs reported increased utilization levels at one of the two improved sites [ 22 ]. Social support for pregnant women has also been found to impact MWH use [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…All 66 records retrieved were observational. There was great variance in terms of study design, with cohort studies [ 9 10 11 12 13 14 15 16 17 18 ], cross-sectional studies [ 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ], intervention studies [ 40 41 42 43 44 45 46 47 48 49 50 ], and unspecified studies included [ 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 ]. Of the 66 studies, only one mentioned any kind costing analysis of MWHs [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 66 records retrieved were observational. There was great variance in terms of study design, with cohort studies [9][10][11][12][13][14][15][16][17][18], cross-sectional studies , intervention studies [40][41][42][43][44][45][46][47][48][49][50], and unspecified studies included . Of the 66 studies, only one mentioned any kind costing analysis of MWHs [47].…”
Section: Resultsmentioning
confidence: 99%